Congenital Chagas disease in a non-endemic area: Results from a control programme in Bergamo province, Northern Italy. Issue 25 (September 2018) - Rodari, Paola; Angheben, Andrea; Gennati, Giorgio; Trezzi, Livia; Bargiggia, Graziano; Maino, Marzia; Ruggeri, Maurizio; Rampello, Stefania; Soavi, Laura; Rizzi, Marco
Abstract: Introduction: In non-endemic countries, one of the most important routes of transmission of Trypanosoma cruzi is vertical transmission. The objective of this work is to report the results of the screening activities for the control of congenital Chagas Disease (CD) implemented in Bergamo province between January 2014 and December 2016. Methods: The programme addressed Bolivian pregnant women settled in Bergamo province. All the eight hospitals offering antenatal and delivery care in that area were involved. We retrospectively calculated the coverage rate of the screening programme, the prevalence of CD in this population, as well as transmission rate to their offspring. Results: During the study period, 376 Bolivian women accounted for 387 deliveries. The coverage rate of serologic screening was 85.6%. Confirmed seropositive women were 28, accounting for a prevalence of CD of 8.7% (95% IC 5.9–11.5). Among 29 children born to positive mothers, one infected child was detected (transmission rate of 4.3%, 95% IC 0–12.6) and treated accordingly. Other 13 children previously born from the same mothers were retrieved and tested for CD: no additional congenital cases were diagnosed. Discussion: Our screening programme presented a high coverage, although widely variable in the different birthing facilities. National guidelines recommending CD testing in pregnant women would help to increase case detection countrywide.